The Effect of Puzzle-Based Learning Media on Students' Critical Thinking in Mathematics Lessons at SDN Kolor II - Rabiyanti, Silva; Ridwan, M.; Zainuddin, Zainuddin (Electronic Journal of Education, Social Economics and Technology, 2024)
This research aims to examine the effect of puzzle-based learning media on students' critical and independent thinking abilities in mathematics lessons. The method used is quantitative experimental with a one group pretest-posttest design. The research sample consisted of 20 students who used pretest posttest. The instrument used was 10 valid questions. After being declared valid, it was then tested for reliability, obtaining a result of 0.785 with a medium category with a reliability coefficient of 0.70, which had been tested for validity and reliability. Data were analyzed using the t-test. The t-count value obtained with a significance value of 0.00 resulted in a t-count of 10.583 with a sig value of 0.00. then to find the t table the researcher used the t distribution with a significance level of ???? = 0.05 or df = N-1 to obtain t = 2.093. So, it can be concluded that 10,583 2.093 or t count t table so it can be concluded that H1 is accepted and H0 is rejected, meaning that mediap puzzle learning has an effect on students' independent critical thinking.